1996
DOI: 10.1128/aem.62.7.2636-2640.1996
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of leucine flux in Lactococcus lactis and its use for the isolation of diacetyl-overproducing strains

Abstract: Diacetyl is a by-product of pyruvate metabolism in Lactococcus lactis, where pyruvate is first converted to ␣-acetolactate, which is slowly decarboxylated to diacetyl in the presence of oxygen. L. lactis usually converts ␣-acetolactate to acetoin enzymatically, by ␣-acetolactate decarboxylase encoded by the aldB gene. We took advantage of the fact that this enzyme also has a central role in the regulation of branched-chain amino acids, to select spontaneous aldB mutants in an unbalanced concentration of leucin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Therefore, several approaches to improve diacetyl production in Lc. lactis have been developed, such as the overexpression of the als genes or ilvBN gene [75] and the inactivation of the ldh [62] or aldB [76,77] genes to increase the metabolic flux towards diacetyl. However, the effects are limited, as the precursors of diacetyl, such as α-acetolactate and pyruvate are at the centre of the metabolic pathways of organisms, and the change of a single gene may not be enough to greatly direct the metabolic flux towards diacetyl production.…”
Section: Metabolic Engineering: Application For Flavour Enhancementmentioning
confidence: 99%
“…Therefore, several approaches to improve diacetyl production in Lc. lactis have been developed, such as the overexpression of the als genes or ilvBN gene [75] and the inactivation of the ldh [62] or aldB [76,77] genes to increase the metabolic flux towards diacetyl. However, the effects are limited, as the precursors of diacetyl, such as α-acetolactate and pyruvate are at the centre of the metabolic pathways of organisms, and the change of a single gene may not be enough to greatly direct the metabolic flux towards diacetyl production.…”
Section: Metabolic Engineering: Application For Flavour Enhancementmentioning
confidence: 99%
“…In addition, these effects may have either immediate or downstream effects. Previous studies have shown how mutations in metabolic enzymes may alter the rates of metabolic flux, while still maintaining reaction fidelity (Goupil et al, 1996). Alternatively, the differences may also be due to differences in the regulatory mechanisms governing protein synthesis or protein expression in the central metabolisms of these strains.…”
Section: Metabolic Profilingmentioning
confidence: 99%
“…The presence of this enzyme may result in growth stimulation, depending on the culture medium (for example in the presence of valine). In contrast to L. lactis, the presence of a-acetolactate decarboxylase is not responsible for inhibition of growth when only leucine is present in the culture medium (Goupil et al 1996). Regulation of branched-chain amino acid biosynthesis by the a-acetolactate decarboxylase in S. thermophilus thus appears to be different from that of L. lactis.…”
Section: Discussionmentioning
confidence: 81%
“…The protein encoded by the aldC gene from strain CNRZ385 showed high homology with the putative a-acetolactate decarboxylase from Streptococcus pneumoniae R6 (75% identity) (Hoskins et al 2001) and with the a-acetolactate decarboxylase from L. lactis subsp. lactis NCDO2118 (61% identity) (Goupil et al 1996). An aacetolactate decarboxylase-negative mutant, named TIL865, was obtained by replacing the wild type gene with a deleted copy.…”
Section: Resultsmentioning
confidence: 99%